Theoretical Analysis on Interferometric Noise in Bidirectional WDM-PON Transmission - Joni Welman Simatupang (Institute of Advanced Engineering and Science, 2013)
In this paper, theoretical analysis on interferometric noise caused by RB and FR in bidirectional single-fiber single-wavelength transmission over the conventional and long-reach WDM-PON is presented. Conventional WDM-PON takes place in access networks, usually for 20 km transmission distance without node amplification. However, for long-reach WDM-PON which is deployed for 100 km or beyond, optical amplification is an indispensable solution to enhance the power budget and prevent fiber nonlinearities that happening in the high power level. However, optical amplifier in long-reach WDM-PON might cause the RB and FR effects worse compare with their effects in conventional ones. It is due to the nature of re-amplification and re-modulation feedback of backscatter and back-reflection lights which existed at the preceding and following of optical amplifier or remote node gain.